Gender and climate adaptation: study of coffee-growing families in canton Olmedo, southern Ecuador - Iñiguez-Gallardo, Veronica (2025)
The analysis of gender dynamics in the context of climate change reveals underlying power structures that shape the implementation of adaptation strategies. Social dynamics intersecting with climate impacts often create vulnerabilities and elicit varied responses between genders. This study presents small-scale research on gender roles in climate adaptation within coffee farming in the Olmedo canton, Loja province, Ecuador. Using qualitative interviews and participant observation, data were collected from coffee-producing families. Findings indicate that coffee production involves gender-differentiated family efforts influenced by power relations and traditional gender roles, with women and their children assuming pivotal roles in adopting climate adaptation measures. These insights contribute empirical evidence for discussions on gender neutrality in climate adaptation policies in South America and highlight the importance of recognizing and leveraging family and community social capital for effective adaptation strategies in coffee farming.